Motion system for a dynamic simulator (2010)
This thesis focuses on developing a motion cueing system for a passenger-training simulator. In this sense, the simulator motion should be defined such that the vestibular Sensor-State of its rider, imitates that of a person on the real vehicle as closely as possible. In order to measure the quality of the Sensor-State imitation specialized error indicators were developed.